Genomic and Molecular Mechanisms of Goat Environmental Adaptation - Ying Lu; Ruoshan Ma; Dongfang Li; Yuyang Gao; Zhengmei Sheng; Jinpeng Shi; Yilong Peng; Zhengdong Gao; Weidong Deng; Xiaoming He (Biology, 2025)
Goats (Capra hircus) are a widely distributed livestock known for their exceptional environmental adaptability. This review presents an integrated overview of recent advances in understanding the genetic and molecular mechanisms underlying goat adaptation to heat, cold, and high-altitude hypoxia. We first discuss the development of high-quality reference genomes, including recent telomere-to-telomere assemblies. We then examine major adaptive genes such as HSP70, ACTHR, EPAS1, SLC2A1, FGF12, and UCP1, and their roles in thermoregulation, oxygen metabolism, and stress resistance. Additionally, the review explores the synergistic role of immune signaling pathways in environmental adaptation, as well as the regulatory effects of epigenetic mechanisms such as DNA methylation, histone modification, and non-coding RNAs. Future efforts should focus on integrating multi-omics data to uncover the complex molecular networks involved in goat adaptation. This comprehensive synthesis offers valuable insights for precision breeding and long-term sustainability in the context of environmental challenges and climate change.